Anonymous Statues: An Empirical Study of Monuments in One American Neighborhood - Stephen Clowney (Washington University Journal of Law and Policy, 2023)
Confederate monuments continue to pose a controversial dilemma for citizens across the United States: should these monuments stay or should they go? Proponents of maintaining standing confederate monuments argue that these statues promote key virtues, honor the soldiers who fought for the South, and preserve local history in its entirety. Alternatively, opponents suggest that the monuments condone treason, venerate a history of racial oppression in the US, and send a message that African Americans are unwelcome in the community that house such monuments. This essay argues that the intense focus on Confederate monuments may have distorted our societal understanding of monuments generally. Specifically, the author questions the ability of a monument to capture and represent community values across time. Focusing on the community of Squirrel Hill in Pittsburgh, Pennsylvania, the author investigated whether members of the community could identify local monuments. The author’s study of Squirrel Hill revealed that many monuments do not stand the test of time but rather fade into obscurity. The author suggests these forgotten monuments highlight the folly of monument protection laws. Several monument protection laws have been enacted amidst the fervor of political controversy in effort to prevent local governments from removing Confederate monuments. This essay highlights the drawbacks of monument protection laws and the impact such laws have on localities: an inability to change memorial spaces along with the changing fabric of local communities.
Keywords: Confederate Monuments; Pittsburgh; Squirrel Hill; Monument Protection Laws; Monument Removal